2020
DOI: 10.1186/s13063-020-4068-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daesiho-tang on obesity with non-alcoholic fatty liver disease: a study protocol for a randomised, double-blind, placebo-controlled pilot trial

Abstract: Background: The high prevalence of obesity and non-alcoholic fatty acid disease has become an important public health problem. Daesiho-tang (DST) is an herbal medicine widely used to treat obesity, metabolic syndrome and liver diseases. This pilot study will assess the feasibility of using DST in obese patients with a non-alcoholic fatty liver disease (NAFLD) prior to undertaking a full-scale clinical trial. Methods/design: This is a study protocol for a randomised, double-blind, parallel-group, stratified, pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Of note, serum CA and TC levels in mice with intrahepatic and extrahepatic cholestasis significantly decreased after DCHD intervention. Study results show that DCHD has the potential to treat obesity and nonalcoholic fatty liver disease (Han et al, 2020). Upon DCHD treatment, the triglyceride content in hepatocytes was significantly reduced, and the fat deposition in the liver was reduced (Nakayama et al, 2007;.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, serum CA and TC levels in mice with intrahepatic and extrahepatic cholestasis significantly decreased after DCHD intervention. Study results show that DCHD has the potential to treat obesity and nonalcoholic fatty liver disease (Han et al, 2020). Upon DCHD treatment, the triglyceride content in hepatocytes was significantly reduced, and the fat deposition in the liver was reduced (Nakayama et al, 2007;.…”
Section: Discussionmentioning
confidence: 91%
“…Our network pharmacology-based approach established PPARα as the core element of DCHT’s visual Herb-Compound-Target-Disease network ( Supplementary Figure S4 ). This may explain why DCHT is considered as a treatment of obesity and hyperlipidemia ( Umeda et al, 1989 ; Han et al, 2020 ), since PPARα plays a central role in the onset and progression of these diseases ( Xu et al, 2018 ). Whether DCHT is a direct or indirect PPARα agonist awaits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits multifaceted pharmacological bioactivities against diseases such as pancreatitis, hypercholesterolemia, diabetes, hyperlipidemia, gastritis, habitual constipation, obesity, etc. ( Umeda et al, 1989 ; Yoshie et al, 2004 ; Duan et al, 2017 ; Han et al, 2020 ; Lian et al, 2020 ). Previous clinical study showed that DCHT improved clinical outcome against cholestatic liver injury ( Song et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 DCHD has also been shown to have significant beneficial effects in type 2 diabetes mellitus 26 and nonalcoholic fatty liver disease. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%